Exploration The Candidates of Xenobiotic Degrading Indigenous Bacteria from Probolinggo City Landfill by Using Next Generation Sequencing (NGS) - Qodriyah, Nur Romadhona Lailatul; Sanjaya, Eli Hendrik; Wahab, Roswanira Abdul; Susanti, Evi (Syarif Hidayatullah State Islamic University, 2023)
Soil bacteria from tropical environments play a significant role in resolving various environmental issues, including biodegradation. Exploratory research on biodiversity is crucial to develop and harness the potential of different types of soil bacteria that are highly abundant. The bacterial diversity in landfills is typically high due to the decomposition of organic and inorganic waste, creating a favorable medium for the growth and development of soil bacteria. This study aims to assess the candidates of xenobiotic degrading indigenous bacteria from the Probolinggo City landfill using Next Generation Sequencing (NGS) method. The research stages include: 1) sampling, 2) isolation of genomic DNA from samples using the ZymoBIOMICS DNA MiniPrep Kit from Zymo Research, 3) amplification of isolated DNA with primers 16S 27F – 1429R, 4) sequencing the results of DNA amplification with NGS, 5) downstream analysis of the results using software Pavian Krona Tools, and 6) narrative analysis review to identify the candidates of xenobiotic degrading indigenous bacteria. The results show that soil samples from the Probolinggo City landfill exhibited a high diversity of bacterial communities. Based on NGS analysis, 2400 bacterial species were identified, comprising 56 genera, 17 orders, 4 classes, and 4 phyla, with respective abundances of Proteobacteria (70%), Firmicutes (15%), Planctomycetes (2%), and Cyanobacteria (0,3%). Based on the narrative analysis review, several bacteria in the Probolinggo City landfill exhibited potential as: 1) polypropylene-degrading bacteria, including Bacillus cereus, B. licheniformis and B. thuringiensis. 2) styrofoam degrading bacteria, namely Bacillus amyloliquefaciens, Bacillus cereus, Bacillus firmus and Pseudomonas aeruginosa. 3) total ammonia nitrogen (TAN) reducing bacteria, including Bacillus megaterium. 4) pesticide degrading bacteria Profenofos and Chlorantraniliprole, including Bacillus stearothermophilus. and 5) tannic acid degrading bacteria, including Pantoea dispersa. These results indicate that the Probolinggo City landfill is a good habitat for various xenobiotic-degrading bacteria, then the isolation of specific bacteria can be designed using an appropriate selective medium.